Mobile Applications as a Tool for Tourism Management in Geoparks (Case Study: Potential Geopark Małopolski Przełom Wisły, E Poland) - Agata Kneć; Wojciech Zgłobicki (Land)
One of the most important challenges facing the development of geotourism is the preparation of tourism products that present geoheritage assets. Nowadays, the Internet and various mobile applications are the primary sources of information about the tourist attractions of specific destinations. Key areas of geotourism development are currently geoparks. However, only about 5% of them have their own mobile applications. The objective of this study was to evaluate the existing mobile applications of geoparks, obtain information on tourists’ expectations of such products, and propose an application concept for the area of the potential Geopark Małopolski Przełom Wisły. One of the challenges for the potential geopark is the concentration of tourist traffic, primarily in the vicinity of the town of Kazimierz Dolny, due to the lack of knowledge of tourists about the values of the rest of the territory. The prepared application is the first geotourism product that we believe will become an important source of information for tourists and will help them in deciding which sites to visit during their stay in the aspiring geopark. When made available, it will affect more tourist traffic in places that have been rarely visited so far but have high geoheritage values, which may encourage local communities to support activities for the creation of the geopark.